Dynamical evolution of a five-level atom interacting with an intensity-dependent coupling regime influenced by a nonlinear Kerr-like medium - N. H. Abdel-Wahab; S. M. Zangi; Tamer A. Seoudy; Saeed Haddadi (Scientific Reports, 2024)
Abstract We present an analytical solution for a quantum system characterized by a double $$Λ$$ Λ five-level atom interacting with an intensity-dependent coupling regime, influenced by a nonlinear Kerr-like medium. We also derive the constants of motion through Heisenberg’s equations. Furthermore, the dynamical evolution of the entanglement and quantum coherence between the atom and the field is discussed using linear entropy and $$l_{1}$$ l 1 -norm of coherence. Through a comprehensive examination of the quantum system, it is observed that both the detuning and the Kerr-like parameters exert a significant impact on the degree of entanglement and coherence. However, the impacts of detuning and the Kerr effect become less pronounced when the photon multiplicity is high. In addition, we conduct a comparison between the five-level atomic system and a four-level system, revealing that the number of energy levels has a profound impact on the behavior of entanglement and coherence. These findings highlight the importance of atomic structure and photon multiplicity in controlling and optimizing quantum processes, particularly in applications involving quantum communication and information processing.